Immune challenges and pathogen risks in edible insects: safeguarding health in space life-support systems - Jensen, Annette Bruun; Copplestone, David; Guidetti, Roberto; Heer, Martina; Pittia, Paola; Berggren, Åsa (Frontiers in Physiology, 2025)
As space agencies progress toward long-duration missions and extraterrestrial colonisation, Bioregenerative Life Support Systems (BLSS) have become central to achieving closed-loop sustainability. Edible insects offer a highly efficient protein source suited for BLSS integration, yet the unique stressors of spaceflight, microgravity, ionising radiation, and limited microbial exposure, pose significant risks to insect immunity and pathogen dynamics. This review synthesises current research on insect immune function, microbiome stability, and disease susceptibility under space-relevant conditions, highlighting vulnerabilities introduced by physical, nutritional and behavioural stressors. We emphasise species-specific immune traits, life stage- and sex-dependent responses, and the contribution of natural behaviours and transgenerational immunity to colony resilience. Further, we examine the synergistic effects of the space environment and high-density rearing on pathogen transmission and virulence evolution. Mitigation strategies, including environmental controls, probiotic interventions and biosensor-based health monitoring, are discussed. By identifying critical knowledge gaps, particularly concerning immune suppression under microgravity and radiation, density-driven pathogen evolution, and the stability of behavioural immunity, we propose system-level responses to support robust insect health. Our synthesis advances the framework for designing resilient, health-optimised insect rearing systems for future space missions and terrestrial applications. Ensuring insect immune competence will be essential for ecological stability and food security in extraterrestrial environments.